1996
DOI: 10.1046/j.1365-2796.1996.52872000.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose levels and insulin secretion during a 75 g glucose challenge test in normal pregnancy

Abstract: The results from this study show that the present cut-off values for diagnosis of gestational diabetes mellitus should be revised. Even if some maternal factors might indicate an increased risk for impaired glucose tolerance during pregnancy, they are probably not enough to detect women with gestational diabetes mellitus. Therefore, a screening programme for gestational diabetes should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…In brief, we found no overall significant difference between oral treatment and insulin for the following outcomes (with the numbers in brackets denoting the total number of RCTs and observational studies respectively): rates of preeclampsia (3,6), caesarean delivery (6,8), maternal 2-hour PG (1, 1), maternal mean BG (1,1), maternal HbA 1c (2, 0), induction of labour (3, 1), macrosomia (2,8), LGA (3, 6), perinatal mortality (4, 6), birth trauma (3, 5), hyperbilirubnaemia (3,4), need for phototherapy (2,6), SGA (2, 5), NICU admission (3,8), congenital malformations (3, 6), respiratory distress (3, 5) and 1-minute Apgar score (1,4).…”
Section: Other Outcomesmentioning
confidence: 79%
See 1 more Smart Citation
“…In brief, we found no overall significant difference between oral treatment and insulin for the following outcomes (with the numbers in brackets denoting the total number of RCTs and observational studies respectively): rates of preeclampsia (3,6), caesarean delivery (6,8), maternal 2-hour PG (1, 1), maternal mean BG (1,1), maternal HbA 1c (2, 0), induction of labour (3, 1), macrosomia (2,8), LGA (3, 6), perinatal mortality (4, 6), birth trauma (3, 5), hyperbilirubnaemia (3,4), need for phototherapy (2,6), SGA (2, 5), NICU admission (3,8), congenital malformations (3, 6), respiratory distress (3, 5) and 1-minute Apgar score (1,4).…”
Section: Other Outcomesmentioning
confidence: 79%
“…This failed to take into account the physiological rise in post-prandial glucose (PPG) levels in pregnancy. In a Swedish study, 6 the mean 2-hour plasma glucose (PG) level was 8.0 mmol/l; if the WHO criteria were applied, 18% would have had GDM.…”
Section: The Previous Health Technology Assessment Reviewmentioning
confidence: 99%
“…It has been suggested that gestational hormones are involved in metabolic changes of pregnancy, as hormones of the placental lactogen, growth hormone, and prolactin family enhances insulin production and release, as well as cell proliferation in islets of Langerhans. Simultaneously with the changes in the endocrine and the pancreas, the sensitivity of the maternal tissues for insulin decreases during pregnancy, thereby increasing the demand for insulin [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Early screening during pregnancy is based on one FPG measurement with the same threshold as after 24 weeks of gestation, as FPG varies little during pregnancy [26,27]. Indeed, FPG levels decrease early in pregnancy with only a slight further decrease later on [28].…”
Section: Issues and Proposals For Screening During Early Pregnancymentioning
confidence: 99%
“…The WHO Guideline Development Group also adopted the IADPSG criteria for any time during pregnancy. However, this remains an issue as post-OGTT glucose values have been reported to be lower at week 17 than at week 32 of gestation in women without GDM tested twice during pregnancy [26]. Therefore, the performance of the use of the glucose OGTT threshold combination to diagnose moderate hyperglycaemia during pregnancy is still unknown, and it appears difficult to consider the OGTT an efficient diagnostic test during early pregnancy.…”
Section: Issues and Proposals For Screening During Early Pregnancymentioning
confidence: 99%